O ensino de filosofia como um aporte político no combate às Fake News: a questão da verdade na política em Hannah Arendt - Lopes, Manoel Auriélio de Carvalho (2024)
The problem of Fake News is a preponderant issue, especially when the information and communication sectors are analyzed, since they are present in our daily lives, becoming a means of propagating false news in a massive way with the aim of distorting information facts and manipulate public opinion to obtain political and economic advantages. Thinking about this context, this work presents the contemporary dynamics of Fake News production on social media and its consequences for public space and politics. The discussion proposed here is based on reflections contained in the work of philosopher Hannah Arendt (1906-1975) about the consequences of the systematic production of lies for the political life of contemporary societies. Here, we highlight “The Origins of Totalitarianism” (1951), a book that would consecrate her with the recognition of her writings by the intellectual community. In 1958, the author published the book “The Human Condition”, which is the most philosophically relevant. The work is divided into three parts. At first, there is a description of what totalitarianism was, a government of terror and lies; the concepts of mass society and apoliticality are worked on, exposing the dimension of propaganda and totalitarian organizations, responsible for creating and spreading lies. In the second part, the relationship between politics and truth in Arendt is investigated; factual and political truth; lies [Fake News] are evil in politics. The third part addresses action and public space as “sites” of truth; action and revelation of the agent as a form of resistance to Fake News and action and its faces: unpredictability – irreversibility – forgiveness – promise. From a methodological point of view, the dissertation, in addition to bibliographic research and textual exegesis based on Hannah Arendt's writings on the proposed topic, makes a pedagogical intervention on the topic. There is a need to understand the relationship between politics and the production of lies with the aim of dominating. There is also an understanding of the need to preserve a public space with the aim of guaranteeing the publication of factual and permanent truths.